The Decolonization of Knowledge: Radical Ideas and the Shaping of Institutions in South Africa and Beyond. - Blackie, Mags (Critical Studies in Teaching and Learning, 2024)
Jansen, J.D. and Walters, C.A. 2022. The Decolonization of Knowledge: Radical Ideas and the Shaping of Institutions in South Africa and Beyond. Cambridge: Cambridge University Press.